2002
DOI: 10.1084/jem.20010798
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of T Cell Differentiation in the Murine Gut

Abstract: Gut intraepithelial CD8 T lymphocytes (T-IEL) are distinct from thymus-derived cells and are thought to derive locally from cryptopatch (CP) precursors. The intermediate stages of differentiation between CP and mature T-IEL were not identified, and the local differentiation process was not characterized. We identified and characterized six phenotypically distinct lineage-negative populations in the CP and the gut epithelium: (a) we determined the kinetics of their generation from bone marrow precursors; (b) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
3

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(141 citation statements)
references
References 53 publications
(106 reference statements)
6
132
3
Order By: Relevance
“…Our previous ontogenetic study suggested that this seeding takes place during the first few weeks of life [10]. As mentioned above, a thymic origin of such diversity appears highly likely because local differentiation in the gut mucosa would not be sufficiently effective [14]. Our data also oppose the notion of a strict origin of CD8ab + IEL from a few recirculating random Agstimulated peripheral CD8 + T lymphoblasts [17], as this would not generate the diversity observed here in GF animals.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Our previous ontogenetic study suggested that this seeding takes place during the first few weeks of life [10]. As mentioned above, a thymic origin of such diversity appears highly likely because local differentiation in the gut mucosa would not be sufficiently effective [14]. Our data also oppose the notion of a strict origin of CD8ab + IEL from a few recirculating random Agstimulated peripheral CD8 + T lymphoblasts [17], as this would not generate the diversity observed here in GF animals.…”
Section: Discussioncontrasting
confidence: 55%
“…The murine cryptopatches appear later in ontogeny, around weaning. Although the limited T cell generative capacity of the cryptopatches [13,14] has been taken to explain why CD8aa + IEL are oligoclonal [14], other studies have provided evidence for selection of CD8aa + IEL precursors in the thymus rather than in the cryptopatches [15,16]. Conversely, oligoclonality of CD8ab + IEL reportedly results from random emergence in thoracic duct lymph of a few pre-activated peripheral CD8 + T cells that are subsequently distributed to the gut epithelium [17], but this hypothesis cannot account for the broad CD8 IEL repertoires observed in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using pTa ic staining [6], single-cell PCR [19] and reporter mice [20] are consistent with the possibility that most DN3 thymocytes, which have recently been shown to contain a very small subset of cd precursors [21], express pTa. However, no functional evidence for the presence of pTa in cd precursors has been reported.…”
Section: Tcrb Transgenes Mediate Pta-dependent Allelic Exclusion In Csupporting
confidence: 59%
“…Third, some IELs can recognize and respond to nonclassical major histocompatibility complex molecules [3,4] and heat shock proteins [5], which may be linked to CD8αα expression by IELs. Fourth, the mammalian intestine can promote the differentiation of T cell precursors from bone marrow progenitors [6][7][8], and the intestine appears to provide both contactmediated and humoral components necessary for the maturation of T cells [9]. Consistent with that, developing IELs have receptors for IL-7 and use IL-7 for survival and maturation [10,11].…”
Section: Introductionmentioning
confidence: 79%